Design Information System of Field Experience Practice Using The Waterfall Model - Ahmad Shauri; Supratman Zakir (Knowbase : International Journal of Knowledge in Database, 2023)
The outcomes of the evaluation will show how well students applied their knowledge in the implementation of the field experience practice. Evaluation is an assessment of the preparation and implementation of the learning process, personal and social abilities, and student reports. Based on this, the researcher wants to design an information system of Field Experience Practice (PPL), in order to help students, Supervisors (DPL), and tutor in obtaining information about Field Experience Practice (PPL) easily, quickly and accurately. Design of the Information system uses the R&D or Research and Development method with the development method SDLC or System Development Life Cycle and the Waterfall model. The design of this information system uses the SDLC model which consists of (1) communication, communication to the user to collect data and information about field experience practice according on the user's demands, (2) Planning is the process of creating a strategy for working on software that contains various tasks to be completed, risks that may occur, resources required, ultimate results to be produced, and process timetables, (3) Modeling is the process of turning requirements into a software design so that they may be validated before coding, (4) construction is the coding process of making an information system, (5) Deployment is the final stage in the construction of a software. The results of the research are presented in the form of an information system that is used by administrators, supervisors, tutors, and students.  The results of the validity test were 0.75 with the valid category of 3 experts, the practicality test results were 0.85 with the high category of 3 experts, and the results of the effectiveness test were 0.88 with the high category of 15 students.